Sources and determinants of free sugars intake by 5-year-old Australian children in the SMILE cohort - Ivaturi, A.; Do, L.G.; Giles, L.; Devenish, Gemma; Scott, Jane A.; Ha, D.H.; Golley, R.; Bell, L.K.; Moynihan, P.J. (2024)
Reducing free sugars intake is important for the prevention of dental caries and obesity in children. The study aimed to determine the amount and sources of free sugars known to contribute to dental caries, and identify sociodemographic determinants of intake by children aged 5 years in Australia. Cross-sectional analysis of dietary data from a cohort study, collected using a customized food frequency questionnaire were used to calculate free sugars intake as grams/day and percentage contribution to Estimated Energy Requirement (EER). The percent contribution of food sources to free sugars intake was derived. Sociodemographic determinants of achieving intakes within WHO thresholds (i.e., <5% and <10% Energy were explored with multinomial logistic regression. Complete data were available for 641 children (347 boys, 294 girls). Median (IQR) free sugars intake (g/day) was 31.6 (21.3–47.6) in boys and 28.1 (19.6–47.9) in girls. The median (IQR) percentage contribution to EER was 7.9 (5.4–12.7); 21% and 42% of children had intakes <5% EER and between 5% and <10%, respectively. The main sources of free sugars were: (1) Cakes, Biscuits and Cereal Bars; (2) Sweetened Milk Products (predominantly yoghurts) and (3) Desserts. Maternal university education, single-parent household, and maternal place of birth being Australia or New Zealand were associated with free sugars intake <5% EER. In conclusion, less than a quarter of 5-year-old children in the SMILE cohort achieved the WHO recommendations to limit free sugars to <5% EER. Strategies to lower free sugars intake could target priority populations such migrants, populations with lower levels of education or health literacy and identify areas for intervention in the wider food environments that children are exposed to.